THERMAL AND PHYSICAL FEATURES OF MAGNETIC AND ELECTRIC GRINDING PROCESS OF GAS AND THERMAL PROTECTIVE COATINGS - N. V. Spiridonov; I. O. Sokorov; M. V. Niaroda (Наука и техника)
The paper reveals thermal zones of magnetic and electric grinding process. The influence of electric and physical parameters of magnetic and electric grinding on temperature in the zone of gas and thermal protective coatings has been established in the paper.